Analisis Putusan Majelis Hakim Pengadilan Negeri Balige terhadap Penerapan Hukum Waris Adat Batak dalam Pembagian Hak Waris - Guntur Rapi Sanjaya; Bima Adi Putranto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Patrilineal inheritance, a customary system practiced in various Indonesian traditions, designates inheritance passing through the paternal lineage. However, complications arise when heirs lack male descendants or those recognized as legitimate by customary norms. Customary practices within the community often address these issues. Judicial panels frequently adjudicate disputes related to patrilineal inheritance to ensure equitable resolutions. Judges, empowered by the Judicial Power Law No. 48 of 2009, make decisions based on a comprehensive understanding of the legal framework and case circumstances. A case analysis, specifically Verdict Number 3494 K/Pdt/2016, concerning the inheritance dispute among the Batak Toba customary community, revealed that evidence from documents and testimonies proved the disputed land belonged to the appellants. The land, previously acquired by the appellants' mother through purchase from the Nagari, was not part of the inheritance left by the appellants' grandfather. However, the decision in settling the Batak Toba customary dispute in Verdict Number 3494 K/Pdt/2016 did not align with the principles of patrilineal inheritance customary to the Batak Toba community. This divergence stemmed from the judges' consideration that the disputed land constituted communal property resulting from the marriage between the late Yakob Sitinjak and the late Sanggul Boru Sinaga.